Využití různých expresních systémů pro přípravu rekombinantních glykosyltransferas - Svobodová, Dana (2008)
Tuberculosis is the leading infectious disease cause of death and its victims represent more than a quarter of the world's preventable deaths. Mycobacterium tuberculosis is the bacterium that causes most cases of tuberculosis. Glycosyltransferases are enzymes, which are participant in bind cell wall of Mycobacterium tuberculosis and play an essential role in life strategy of this bacterium. Rv0225 and Rv3782 are possible glycosyltransferases from bacterium Mycobacterium tuberculosis. The aim of this project is gaining the studied glycosyltransferases in recombinant form, as pure as possible, in order to perform the structural and functional characterization. Understanding the structure-functional relations and the mechanism of glycosyltransferase catalysis is important for designing ways of inhibition of the Mycobacterium tuberculosis glycosyltransferases, a potential great help in treatment of tuberculosis.